IMF Survey, Volume 31, Issue 10. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2002)
Earlier this year, Abdoulaye Bio-Tchane took over as Director of the IMF's African Department. Before joining the IMF staff, he was Benin's Minister of Finance and Economy. He began his career as an economist in the Central Bank of West African States (BCEAO), where he rose to become Director of the Economic and Monetary Survey Department. He recently returned from a one-week trip with IMF Managing Director Horst Kohler to Burkina Faso, Cote d'Ivoire, Democratic Republic of the Congo, Ghana, and Tanzania. At the end of the trip, on May 3, Kohler announced that the IMF plans to establish five regional centers in Africa to strengthen locally based technical assistance and training.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet